Positional Relationship between Two Microcatheters according to the Navigation Sequence within the Curved Vessel in Neuroendovascular Procedures - Ohshima, Tomotaka; Koiwai, Megumi; Matsuo, Naoki; Miyachi, Shigeru (Asian Journal of Neurosurgery, 2024)
Objective In neuroendovascular treatment, there are many opportunities to guide multiple catheters into the intracranial blood vessels. We report the relationship between two microcatheters according to the guiding order with experimental in vitro studies.Materials and Methods We hypothesize that in a bent blood vessel such as a paraclinoid region of the internal carotid artery, the catheter that was first guided tended to pass through the inside, and the catheter that was guided later tended to pass through the outside. The in vitro verification was performed using a microcatheter and a balloon catheter in a silicone vascular aneurysmal model.Results As a result, it was found that the two catheters were arranged according to our hypothesis. This finding was also observed during the actual operation of balloon-assisted coil embolization.Conclusion The positional relationship between the two catheters according to the navigation order is very important, in particular during balloon-assisted coiling and stent-assisted coiling via a jailed microcatheter.
Keywords: endovascular treatment; intracranial aneurysms; coil embolization; microcatheter